Characterisation of circulatiing HIV-1 subtypes and drug resistance-associated mutations in protease and reverse transcriptase genes among HIV-1 patients in Kelantan - Tengku Mohd Ariffin, Tengku Ahmad Akram (2015)
Human Immunodeficiency Virus (HIV) infection is one of major infectious diseases in Malaysia. A number of studies pertaining to genetic diversity and drug resistance surveillance have been performed in Malaysia, especially in Kuala Lumpur and Selangor. However, in the past two decades, there is a lack of knowledge on HIV-1 diversity and drug resistance among people living with HIV (PLHIV) in Kelantan although this state is among the top three states reporting the highest number of new HIV cases annually. This study demonstrated that among PLHIV in Kelantan, there were six HIV-1 subtypes circulating in different risk groups. These subtypes were CRF33_01B, B‟ subtype, CRF01_AE, CRF53_01B, CRF54_01B and URF CRF01_AE/B. Additionally, this study showed the predominance of CRF33_01B subtype among adult and paediatric patients and all risk populations (Intravenous drug use (IDUs), heterosexual contact and vertical transmission). Sharing needle was found to be the main contributor for HIV dissemination in study population, different than other studies in Malaysia which reported sexual contact as the main factor of HIV transmission since 12 years ago. Majority of HIV patients continued to be male who acquired the infection mostly through sharing needle. In contrast, female patients were infected with HIV via sexual contact. Drug resistance analysis was carried out based on Stanford HIV drug resistance database. From 25 treatment-naive patients, 40% were infected by HIV-1 containing at least one transmitted Resistance-associated mutations (RAMs). When analysed against World Health Organisation (WHO) consensus, the value was reduced to 16%. Twenty transmitted RAMs were harvested from treatment-naive patients, with 60% were associated with Nonnucleoside Reverse Transcriptase Inhibitor (NNRTI), and 20% each were associated with Nucleoside/Nucleotide Reverse Transcriptase Inhibitor (NRTI) and Protease Inhibitor (PI). The most commonly observed transmitted mutation was V179D/T (16%), which may reduce drug susceptibility to NNRTI. Meanwhile, according to Stanford HIV drug resistance database, 79.7% of patients currently receiving treatment carrying HIV-1 containing acquired RAMs against NRTI, NNRTI and PI. Among treated patients, 251 acquired RAMs were obtained with more than half were associated with NRTI (55.4%), followed by NNRTI (37.1%) and PI (7.6%). The most frequent mutations observed were M184I/V (40.6%), K103N/R/S (37.5%), T215F/H/I/V/Y (35.9%) and D67G/H/N (31.3%). Only K103N/R/S was associated with NNRTI while the rest of mutations were associated with NRTI. The present study confirms the high prevalence of CRF33_01B in Kelantan state and reveals a high genetic diversity with the presence of newly described HIV-1 Circulating Recombinant Forms (CRFs) and HIV-1 Unique Recombinant Forms (URFs). Continuous molecular surveillance should be performed to monitor further emergence of HIV-1 URFs. Result from drug resistance analysis enhances the knowledge pertaining to Highly Active Antiretroviral Therapy (HAART) performance, helps in designing effective HAART strategy on treatment-naive and treated patients and subsequently emphasises the need to commence drug resistance testing prior to starting or changing HAART treatment.